The Influence of Character, Capacity, and Collateral on the Causes of Non-Performing Loan - Putu Ayu Diah Widari Putri; Nyoman Yudha Astriayu Widyari (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2024)
Cases of Non-Performing Loan that have occurred in Indonesia to date are classified as a high percentage. Cases of Non-Performing Loan in Indonesia have increased since the COVID-19 pandemic. One of the credit providing institutions in Indonesia, namely cooperatives, is also facing problems related to a spike in Non-Performing Loan cases, especially during pandemic. By looking into the causes of non-performing loans, one can lower the risk of non-performing loans. Because basically, before providing credit services, banks must first analyse whether the prospective debtor can be trusted or relied upon. This type of research uses quantitative approach method with data collection techniques using research instruments in the form of questionnaires. Purposive sampling is the sampling technique used in this research for 157 people. The data analysis technique in this research uses multiple linear regression tests. The results of hypothesis testing in the research show that character has a negative effect on the causes of Artha Mandala Cooperative’s NPL, capacity has a negative effect on the causes of Artha Mandala Cooperative’s NPL, and collateral have a negative effect on the causes of Artha Mandala Cooperative’s NPL. That character, capacity, and collateral have a negative influence on the causes of Non-Performing Loan Artha Mandala Cooperative. The suggestions that can be given are to Artha Mandala Cooperative to carry out regular checks, such as once every 3 months or 6 months, regarding creditors' economic conditions to anticipate opportunities for credit congestion to occur.